The benefits of aerobic training for improving quality of life: A Critical Review of Study - Agung Wahyu Permadi (Warmadewa University, 2019)
Aerobic exercise is currently the safest sport for both young and old people. This is because aerobic training provides tiered and targeted training and acts specifically on several muscles. The general purpose of aerobic exercise isto train the body to exercise without stress and excessive psychological disturbances. Then, aerobic exercise is also done in stages such as stretching, strength, and balance of various types of muscle and joint flexibility exercises. This is very useful for the elderly to avoid injury during aerobic training and is able to reduce the psychological disorders that are often experienced by the elderly. In this review, we conclude that aerobic exercise can have a good impact especially on stress levels on quality of life in the elderly.